SIGNIFIKASI SPIRITUALITAS HOLISTIK DALAM KIDUNG RUMEKSO ING WENGI KARYA SUNAN KALIJAGA - Lestari, Sri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
Oral literature is one of the cultural elements that is still passed down from generation to generation. This study aims to describe the significance of holistic spirituality in Sunan Kalijaga's Song Rumekso ing Wengi. This research is a qualitative research. The data in this study consisted of documents and interviews. Collecting data in this study by interview and document analysis. The data validation technique uses theory and method triangulation. Meanwhile, the data analysis technique used the interactive model of Miles and Hubermann, and the markers were Roland Barthes. The results showed that the song rumeksa ing wengi is a rejection mantra taught by Sunan Kalijaga to his followers. Until now, there are still people who develop the song and the practice of the song as a medium of prayer by paying attention to the aspect of tolerance. There are various values ​​that are contained such as ethics of understanding, returning to God, ethics of prayer, and self-control.